Prevalence of substance use disorder comorbidity among individuals with eating disorders: A systematic review and meta-analysis. (March 2019) - Bahji, Anees; Mazhar, Mir Nadeem; Hudson, Chloe C.; Nadkarni, Pallavi; MacNeil, Brad A.; Hawken, Emily
Highlights: Our recent and comprehensive meta-analysis of comorbid substance use disorder (SUD) in individuals with eating disorders measured the pooled lifetime and current prevalence of any comorbid SUD, which were 21.9% (95% CI 16.7–28.0) and 7.7% (95% CI 2.0–25.8), respectively. Tobacco (36.1 ± 23.1%), caffeine (23.8 ± 12.5%), and alcohol (20.6 ± 16.0%) were among the most prevalent comorbidities. Higher prevalence was observed in all-female samples, primarily Caucasian samples, and binge-purge presentations. There are significant prognostic, diagnostic, and treatment implications for patients who have comorbid substance use disorders. Abstract: Objective: : Although prior meta-analyses have significantly enriched the available literature on the comorbidity of substance use disorders (SUD) among individuals with eating disorders (ED), there have been few, recent, comprehensive reviews, and limited meta-analyses that include a range of SUDs. Method: : In accordance with the PRISMA guidelines, six electronic databases were searched, and a total of 1013 articles were identified using a combination of search terms to identify relevant prevalence studies: eating disorder, substance-related disorder, drug dependence, drug abuse, drug addiction, substance abuse, and prevalence. After two authors screened articles and extracted data independently, 43 articles met inclusion criteria. Data was coded, and a risk of bias assessment was conducted for each included study. Meta-analysis and moderator-analysis was carried out using random-effects modelling. Results: : The pooled lifetime and current prevalence of any comorbid SUD was 21.9% (95% CI 16.7–28.0) and 7.7% (95% CI 2.0–25.8), respectively. Tobacco (36.1 ± 23.1%), caffeine (23.8 ± 12.5%), and alcohol (20.6 ± 16.0%) were the most prevalent SUD comorbidities. Higher prevalence was observed in all-female samples, primarily Caucasian samples, and binge-purge presentations. Neither lifetime nor current prevalence were associated with age. Discussion: : These results suggest that individuals with eating disorders should be regularly screened and offered treatment for substance use disorders concurrently during treatment for ED.